Design of Encryption Block for High Speed Low Power Blowfish Cipher - Meshram, Sneha D.; Gokhale, U. M. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Data security always been important in all aspects of life. Data contain important information that must be protected from unauthorized access. As technology continues to dominance various operations in our day to day life so it is important. Reprogrammable devices are highly irresistible option for hardware execution of encryption algorithm. It is essential because these devices enhance cryptographic algorithm ability, physical security. Therefore this paper scrutinize the most important process in cryptographic algorithm i.e. Encryption. Here we used the Blowfish algorithm which is block cipher. All the basic blocks of this block cipher is designed by using VHDL.